Attributions of People with Intellectual Disabilities of Their Own or Other Clients' Challenging Behavior: A Systematic Review of Qualitative Studies. Issue 3 (31st October 2019) - van den Bogaard, K.J.H.M.; Lugtenberg, M.; Nijs, S.; Embregts, P.J.C.M
ABSTRACT: Introduction : As opposed to studies focusing on staffs' attributions of challenging behavior (CB), relatively few studies have looked at how people with intellectual disabilities (ID) attribute such behaviors themselves, and a systematic overview is currently lacking. The aim of this review was to synthesize the evidence from qualitative studies on the attributions people with ID have concerning their own or other clients' CB. Methods : A systematic literature search was conducted in Embase, Medline Ovid, Web of science, Cochrane CENTRAL, PsychINFO Ovid, and Google Scholar. Studies were included if they focused on people with ID who report on attributions of their own or other clients' actual CB. The methodological quality of the studies was assessed using the Critical Appraisal Skills Programme (CASP) checklist. Result : A total of 10 studies were included. Three main types of factors subdivided in 13 sub-types were reported by clients as potential causes of CB: interpersonal factors (1 support staff, 2 other clients, 3 general, 4 life history), environmental factors (1 ward, 2 social exclusion, 3 situational factors) and intrapersonal factors (1 syndrome or diagnosis, 2 medical or physical symptoms, 3 psychological reasons, 4 emotions and feelings, 5 coping, 6 other). Conclusions : This thematic synthesis shows that clients with ID report a diverse range of attributions regarding their own or other clients' CB. This spectrum can be used as a framework for interpreting CB and for the development of appropriate support systems for people with ID demonstrating CB.